Exploring The Potential Of Mobile-Assisted Language Learning (Mall) Applications In Developing English Vocabulary Skills - Azhariah Rachman; Muhammad Zulfikrie Taswin; Sitti Agustina; Ira Zulfa; Abraham Manuhutu (Departement of Mathematics Education, 2023)
This literature review aims to investigate the potential of Mobile-Assisted Language Learning (MALL) applications in the development of English vocabulary skills. As mobile devices become increasingly integrated into our daily lives, their potential as tools for language learning has gained significant attention. This article explores the current research and examines the effectiveness of MALL applications in enhancing English vocabulary acquisition. The review highlights the advantages, challenges, and implications of using MALL applications and offers recommendations for educators, researchers, and developers to optimize the utilization of these applications for improving English vocabulary skills.